226k views
24 votes
Rewrite as equivalent rational expressions with denominator (a−7)(a−2)(a+8):

Rewrite as equivalent rational expressions with denominator (a−7)(a−2)(a+8):-example-1
User Wwilczyn
by
5.1k points

1 Answer

3 votes

Answer:


(3(a + 8))/((a - 7)(a - 2)(a + 8))


(8a(a - 2))/((a - 7)(a - 2)(a + 8))

Explanation:


(3)/(a^2 - 9a + 14) =


= (3)/((a - 7)(a - 2))


= (3(a + 8))/((a - 7)(a - 2)(a + 8))


(8a)/(a^2 + a - 56) =


= (8a)/((a + 8)(a - 7))


= (8a(a - 2))/((a - 7)(a - 2)(a + 8))

User Camila Macedo
by
4.6k points